Ca2+ Channels Involvement in Low-Frequency Stimulation-Mediated Suppression of Intrinsic Excitability of Hippocampal CA1 Pyramidal Cells in a Rat Amygdala Kindling Model. (15th May 2019) - Ghotbeddin, Zohreh; Heysieattalab, Soomaayeh; Borjkhani, Mehdi; Mirnajafi-Zadeh, Javad; Semnanian, Saeed; Hosseinmardi, Narges; Janahmadi, Mahyar
Abstract: Low-frequency stimulation has demonstrated promising seizure suppression in animal models of epilepsy, while the mechanism of the effect is still debated. Changes in intrinsic properties have been recognized as a prominent pathophysiologically relevant feature of numerous neurological disorders including epilepsy. Here, it was evaluated whether LFS can preserve the intrinsic neuronal electrophysiological properties in a rat model of epilepsy, focusing on the possible involvement of voltage-gated Ca 2+ channels. The amygdala kindling model was induced by 3 s monophasic square wave pulses (50 Hz, 1 ms duration, 12times/day at 5 min intervals). Both LFS alone and kindled plus LFS (KLFS) groups received four packages of LFS (each consisting of 200 monophasic square pulses, 0.1 ms pulse duration at 1 Hz with the after discharge threshold intensity), which in KLFS rats was applied immediately after kindling induction. Whole-cell patch-clamp recordings were made in the presence of fast synaptic blockers 24 h after the last kindling stimulations or following kindling stimulations plus LFS application. In the KLFS group, both the rebound excitation and kindling-induced intrinsic hyperexcitability were decreased, associated with a regular intrinsic firing as indicated by a lower coefficient of variation. The amplitude of afterdepolarization (ADP) and its area under the curve were both decreased in the KLFS group compared to the kindled group. LFS prevented the increasing effect of kindling on Ca 2+ currents in the KLFS group. Findings provided evidence for a novel form of epileptiform activity suppression by LFS in the presence of synaptic blockade possibly by decreasing Ca 2+ currents. Graphical abstract: Unlabelled Image Highlights: Amygdala kindling alters intrinsic excitability of CA1 pyramidal neurons Low-frequency stimulation (LFS) prevents the induction of neuronal intrinsic hyperexcitability by amygdala kindling. Induction of amygdala kindling enhances Ca2 + channel current in CA1 pyramidal neurons LFS prevented the increasing effect of epileptiform activity on Ca 2+ currents.